Evaluation of rotigotine transdermal patch for the treatment of apathy and motor symptoms in Parkinson's disease. Issue 1 (December 2016) - Hauser, Robert; Slawek, Jaroslaw; Barone, Paolo; Dohin, Elisabeth; Surmann, Erwin; Asgharnejad, Mahnaz; Bauer, Lars
Abstract Background This multicenter, double-blind, placebo-controlled study assessed the efficacy of rotigotine transdermal patch on apathy and motor symptoms in patients with Parkinson's disease (PD). Methods Patients with PD-associated apathy (Unified Parkinson's Disease Rating Scale [UPDRS] I item 4 [motivation] ≥2 and patient-rated Apathy Scale [AS] ≥14) were randomized 1:1:1 to "low-dose" rotigotine (≤6 mg/24 h for early PD [those not receiving levodopa] or ≤8 mg/24 h for advanced PD [those receiving levodopa]), "high-dose" rotigotine (≤8 mg/24 h for early PD or ≤16 mg/24 h for advanced PD), or placebo, and maintained at optimal/maximal dose for 12 weeks. Coprimary efficacy variables were: change from baseline to End of Maintenance in patient-rated AS and UPDRS II + III total score. Recruitment was stopped after an interim futility analysis; therefore, all p values are exploratory. Results Of 122 patients randomized, 81.1 % completed the study (placebo, n = 32/40 [80.0 %]; low-dose rotigotine, n = 30/41 [73.2 %]; high-dose rotigotine, n = 37/41 [90.2 %]). No treatment difference was observed in the change in patient-rated AS (least squares mean [95 % confidence interval (CI)] difference: low-dose, 0.04 [−2.42, 2.50], p =0.977; high-dose, −0.22 [−2.61, 2.18], p = 0.859). Rotigotine improved UPDRS II + III total scores versus placebo (least squares mean [95 % CI] treatment difference: low-dose, −7.29 [−12.30, −2.28], p = 0.005; high-dose, −6.06 [−10.90, −1.21], p = 0.015), and the "mood/apathy" domain of the Non-Motor Symptom Scale as rated by the investigator (secondary outcome). The most frequent adverse events in rotigotine-treated patients were application site reactions, somnolence, and nausea. Conclusions Rotigotine did not improve PD-associated apathy as rated by the patient but provided clinically relevant improvement in motor control and activities of daily living. Trial registration ClinicalTrials.gov identifierNCT01782222 . Trial registration date: January 30, 2013.